Major locus on ECA18 influences effectiveness of GonaCon vaccine in feral horses. (February 2023) - Thompson, Melissa A.; McCann, Blake E.; Simmons, Rebecca B.; Rhen, Turk
Abstract: Contraceptive vaccines are used to reduce birth rates in wild and feral animal populations. While the immunocontraceptive GonaCon-Equine has proven effective in reducing fertility among female feral horses, there is individual variation in the duration of infertility following treatment. To identify genetic factors influencing the effectiveness of GonaCon-Equine, we conducted a genome-wide association study of 88 mares from a feral population genotyped using the Illumina GGP Equine 70k SNP array. Contraceptive treatment schedules and long-term foaling rates have been recorded for each individual. We used mixed linear models to control for relatedness among mares. We found a significant association (p < 5 ×10 -8 ) with a locus on equine chromosome 18. The most likely candidate genes in this region are STAT1 and STAT4, which are both involved in immune system function. Variation in STAT function could affect the immune response to the vaccine, leading to variation in contraceptive efficacy. Additional SNPs reaching a less stringent threshold of significance (p < 5 ×10 -6 ) were located on other chromosomes near known immune system genes, supporting the hypothesis that variation in immunocontraceptive efficacy can be attributed to genetic variation in immune response rather than fertility genes. Highlights: Duration of infertility after GonaCon-Equine treatment varies among individuals. Major locus on ECA18 is significantly associated with this variation. Candidate genes (STAT1, STAT4, IKZF1, PTPN22) involved in immune system function. First evidence of genetic factors influencing immunocontraception efficacy.